Career Development Assessment Tools for Indonesian Adolescents: A Psychometric Study - Rizky Mayesita Aryance Abel; Andriyani Emilia Lay; Khetye Romelya Saba; Khatarina E.P Korohama; Putu Agus Indrawan; Paulinus A.S Uda; I Putu Agus Apriliana (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Indonesian adolescents face critical challenges in making career decisions, while limited access to culturally valid assessment tools further complicates their efforts to navigate this important developmental task. This study aimed to validate a career development assessment tool by 1) exploring its latent factor structure, 2) confirming the factorial model, and 3) evaluating its internal consistency reliability. Employing a quantitative cross-sectional survey design, a total of 743 adolescents completed an online 34-item instrument. Data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). These results find EFA identified a stable three-factor structure comprising personal goals, self-efficacy beliefs, and outcome expectations, consistent with the Social Cognitive Career Theory framework. These dimensions demonstrated theoretical coherence and empirical support through strong item loadings and meaningful inter-factor correlations. The CFA further supported the model’s adequacy, with fit indices indicating a good correspondence between the hypothesized structure and observed data. A total of 23 items showed substantial contributions to their respective latent constructs, confirming the instrument’s construct validity, with satisfactory internal consistency across all dimensions. The validated 23-item instrument thus offers a theoretically grounded and psychometrically robust contribution to career guidance practices and educational planning within the Indonesian context.